MRI and contrast-enhanced ultrasound imaging for evaluation of focal irreversible electroporation treatment: results from a phase I-II study in patients undergoing IRE followed by radical prostatectomy - van den Bos, Willemien (Eur Radiol, 2015)
OBJECTIVES: Irreversible electroporation (IRE) is an ablative therapy with a low side-effect profile in prostate cancer. The objective was: 1) To compare the volumetric IRE ablation zone on grey-scale transrectal ultrasound (TRUS), contrast-enhanced ultrasound (CEUS) and multiparametric MRI (mpMRI) with histopathology findings; 2) To determine a reliable imaging modality to visualize the IRE ablation effects accurately. METHODS: A prospective phase I-II study was performed in 16 patients scheduled for radical prostatectomy (RP). IRE of the prostate was performed 4 weeks before RP. Prior to, and 4 weeks after the IRE treatment, imaging was performed by TRUS, CEUS, and mpMRI. 3D-analysis of the ablation volumes on imaging and on H&E-stained whole-mount sections was performed. The volumes were compared and the correlation was calculated. RESULTS: Evaluation of the imaging demonstrated that with T2-weighted MRI, dynamic contrast enhanced (DCE) MRI, and CEUS, effects of IRE are visible. T2MRI and CEUS closely match the volumes on histopathology (Pearson correlation r = 0.88 resp. 0.80). However, IRE is not visible with TRUS. CONCLUSIONS: mpMRI and CEUS are appropriate for assessing IRE effects and are the most feasible imaging modalities to visualize IRE ablation zone. The imaging is concordant with results of histopathological examination. KEY POINTS: • mpMRI and contrast-enhanced ultrasound are appropriate imaging modalities for assessing IRE effects • mpMRI and CEUS are the most feasible imaging modalities to visualize IRE ablation zone • The imaging is concordant with results of histopathological examination after IRE • Grey-scale US is insufficient for assessing IRE ablations